HADIST DAKWAH: URGENSI NIAT DALAM DAKWAH - BAGUS PRAYUGO BAGUS (Department of Islamic Communication and Broadcasting - Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Abstract: Intention comes from Arabic, namely an niyat which is the plural form of niyah. Etymologically, intention means al qoshdu which means will. Intention also means al'azm, which is a strong desire. An-Nawawi said,